BRD4 degradation blocks expression of MYC and multiple forms of stem cell resistance in Ph+ chronic myeloid leukemia. Issue 9 (18th July 2022) - Peter, Barbara; Eisenwort, Gregor; Sadovnik, Irina; Bauer, Karin; Willmann, Michael; Rülicke, Thomas; Berger, Daniela; Stefanzl, Gabriele; Greiner, Georg; Hoermann, Gregor; Keller, Alexandra; Wolf, Dominik; et al.
Abstract: In most patients with chronic myeloid leukemia (CML) clonal cells can be kept under control by BCR::ABL1 tyrosine kinase inhibitors (TKI). However, overt resistance or intolerance against these TKI may occur. We identified the epigenetic reader BRD4 and its downstream‐effector MYC as growth regulators and therapeutic targets in CML cells. BRD4 and MYC were found to be expressed in primary CML cells, CD34 + /CD38 − leukemic stem cells (LSC), and in the CML cell lines KU812, K562, KCL22, and KCL22 T315I . The BRD4‐targeting drug JQ1 was found to suppress proliferation in KU812 cells and primary leukemic cells in the majority of patients with chronic phase CML. In the blast phase of CML, JQ1 was less effective. However, the BRD4 degrader dBET6 was found to block proliferation and/or survival of primary CML cells in all patients tested, including blast phase CML and CML cells exhibiting the T315I variant of BCR::ABL1. Moreover, dBET6 was found to block MYC expression and to synergize with BCR::ABL1 TKI in inhibiting the proliferation in the JQ1‐resistant cell line K562. Furthermore, BRD4 degradation was found to overcome osteoblast‐induced TKI resistance of CML LSC in a co‐culture system and to block interferon‐gamma‐induced upregulation of the checkpoint antigen PD‐L1 in LSC. Finally, dBET6 was found to suppress the in vitro survival of CML LSC and their engraftment in NSG mice. Together, targeting of BRD4 and MYC through BET degradation sensitizes CML cells against BCR::ABL1 TKI and is a potent approach to overcome multiple forms of drug resistance in CML LSC.